Budidaya Cabai sebagai Komoditas Unggulan: Peluang, Kendala, dan Strategi Pengembangan Hortikultura di Banjar Agung, Provinsi Banten - Khatulistiwa, Iksan; Sonjaya, Ferdinansyah; Ramadhan, Abian Galin; Pamela, Vega Yosepha; Najah, Zulfatun (Fakultas Pertanian, Universitas Pattimura, 2025)
Indonesia, as an agrarian nation, relies on its agricultural sector to fulfill food needs, enhance public welfare, and generate national foreign exchange. Chili stands out as a high-value horticultural commodity, serving not only as a culinary spice but also as a raw material for the food and pharmaceutical industries. This study aims to describe the utilization of agricultural land for chili cultivation in Banjar Agung District, Serang City, Banten Province. The research employs a descriptive approach using secondary data from the Jabon Adiyasa Mandiri farmer group. Findings indicate that chili cultivation covers 3 hectares, equally distributed among cayenne pepper, curly chili, and large chili, each yielding 200 kg per hectare. This productivity is relatively low compared to the national average of 500–1,000 kg/ha. Key factors contributing to low yields include suboptimal cultivation techniques, limited technology, climate change, and pest and disease outbreaks. These findings highlight the necessity for improved agricultural technology and practices to ensure self-sufficiency and sustainability in chili cultivation within the region.